Perancangan dan Implementasi Augmented Reality Tanjak Melayu menggunakan metode MDLC - Jimmy Pratama; Muhammad Zaki (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
Tanjak is an accessory used by the people at the time the Malay kingdom stood. However, the traditional era began to develop into the era of digital culture and Malay heritage is fading. The purpose of this study is a form of concern if culture is simply forgotten without any attempt to reintroduce it. With today's technology, climbs can be visualized using technology that can display 3D objects in the real world. This technology is usually called augmented reality, so tanjak can be known to the wider community which can be accessed using smart devices that support augmented reality and use the operating system android. This research itself uses the method Multimedia Development Life Cycle. In the process using a variety of software such as cinema4D, Unity, adobe illustrator. The output obtained is an application augmented reality with a .apk extension that can be downloaded using the google play store